Problematika Yuridis Pelepasan Hak Milik Menjadi HGB pada Perumahan Subsidi di Indonesia - Natanael Klose Hasiholan Simbolon; Elita Rahmi; Fitria Fitria (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2026)
The conversion of freehold land rights into building use rights (HGB) in Indonesia’s subsidized housing program raises various legal issues. This study aims to analyze the mechanism for converting as well as legal certainty following the enactment of Ministerial Regulation ATR/BPN No. 5 of 2025. The research method employed is normative legal research using a legislative and conceptual approach through a literature review of primary, secondary, and tertiary legal sources. The research results indicate that the shift in mechanism from a system of rights reduction to the transfer of rights and the granting of new rights has created procedural complexities and legal ambiguity regarding the transitional phase of state-owned land prior to the issuance of HGB. In conclusion, harmonization of regulations and clarification of transitional norms are necessary so that the mechanism for the relinquishment of land ownership rights to HGB can provide legal certainty, administrative efficiency, and support the success of sustainable society development in the subsidized housing sector.